A Study on the job Analysis for New Nurse - Moon Sil Kim; Ji Ho Song; Bun Han Kim; Seung Hee Lee (Journal of Educational Evaluation for Health Professions, 2004)
This study is empirical and descriptive one for analysing the nurse's job. This study used the methods of making the job descriptions and survey research about the nurses' perception of importance in their job and the frequency of job performance. The results were in following: the research divided the job of new nurse into 11 duties. And duties include the 65 tasks and 446 task elements. According to the survey research on the nurses' perception of importance and the frequency of job performance, the elements graded higher than 2.5 point in importance perception, were 47 elements(10.5%). And the elements from 2.0 to 2.5 were 93 elements(18.8%). Regarding the frequency of job performance, the 56 elements were graded higher than 2.5 point on average(12.6%), and 84 elements were from 2.0 to 2.5(18.8%). Especially, the elements which grade higher than 2.5 point in both two items, were 31 elements(7.0%). Based on these results, the elements graded higher than 2.0 point were grouped to the core competencies for registered nurse, these could be core concepts to develop the questions for national examination for nurse's registration.